Estrategias de marketing para los servicios de restauración afectados por la influencia de la Covid-19, en el destino turístico Manta, Manabí, Ecuador - Vergara Mendoza, Javier David (2023)
Tourist establishments that provide services go through an updating process to stay in the market. The purpose of the research is to propose marketing strategies for restaurant services affected by the spread of COVID-19, in Manta destination. Indeed, the study contemplates three fundamental phases starting with the diagnosis of the catering services, through the characterization sheet allowing the identification of fundamental elements. The second phase, evaluation of aspects that affected the catering services, was carried out through the review of official documents, interviews with representatives of the Tourism department of the GAD Manta together with the application of 196 surveys that were aimed at tourists who previously visited the establishments selected, in effect through the analysis it was known that 88.92% of the tourist companies are in the micro group and that 40% of the establishments are independent. Another of the activities that was complemented with the aforementioned actions was the analysis of the demand and supply in Manta city. The last phase emphasizes the determination of conclusive Marketing strategies based mainly on the results of the SWOT matrix, the interview and surveys. It is concluded that the strategies will reward the improvement of the development of restaurant services since it is the basis for the establishments to continue with their reopening and improve their economy.